Body Build of Polytechnic Pupils and Tractor Drivers - Gościcka, Danuta; Klaus, Ewa (Anthropological Review, 1988)
The weight-and-height Rohrer’s index was calculated for 102 pupils of the Polytechnic for Agiculture Mechanization and 160 tractor drivers employed in state-owned farms. It was found out that with age the pupils developed a tendency towards an athletic body build, whereas the tractor drivers with the passage of years of work a tendency towards a pyknic body build.